Yeast immobilization effects on the biochemical characteristics of rice wine - Arguilla, Mazel Crisely F.
ABSTRACT The effects of Saccharomyces cerevisiae immobilization on the biochemical profile of rice wine during fermentation and 30 -day storage at 4°C and 25°C were investigated. Three fermentation experiments were carried out by different modalities of inoculums- free yeast cells, immobilized yeast cells and pre-incubated immobilized yeast. During rice wine production, immobilized cells and pre-incubated immobilized cells caused a significant (p<0.05) increase in the fermentation rate as evidenced by the higher substrate uptake of these two systems compared with free cells. Concomitant with this result, the rice wine produced by the immobilized biocatalyst had a higher (p<0.05) alcohol concentration (17.44-18.94% v/v) than those obtained from free yeast cells. Yeast immobilization resulted to clearer wines and low cell counts. Other biochemical parameters were at normal level. Immobilization had no consistent effect on aging and storage properties of rice wine except for increased volatile acidity and stable yeast and mold count. The results established that yeast immobilization improved fermentation efficiency and quality of rice wine.